An overview on "cellular cannibalism” with special reference to oral squamous cell carcinoma - Jain, M. (Experimental Oncology, 2015)
Cellular cannibalism has been defined as a large cell engulfing a slightly smaller one within its cytoplasm. It has been described in various cancers like bladder cancer, breast cancer, lung cancer, gastric cancer, oral squamous cell carcinoma. Cellular cannibalism has been well correlated with anaplasia, tumor aggressiveness, grading and metastatic potential. Present review focuses on significance of cannibalism in relation to cancer with special emphasis on oral squamous cell carcinoma. Key Words: cannibalism, phagocytosis, cancer, oral squamous cell carcinoma.